DETERMINATION OF SHELF LIFE USING ACCELERATED SHELF LIFE TEST (ASLT) METHOD ON INSTANT POWDER PROBIOTIC ORANGE SWEET POTATO FREEZE DRY - Yulia Nunung; Rubiyanti Rani; Tjitda Putra Jiwamurwa Pama; Mbunga Dominus (Pharmacoscript, 2026)
Probiotic beverages produced using freeze-drying techniques are commonly developed to extend shelf life. In this study, instant probiotic powder made from orange sweet potato was prepared using the freeze-drying process at -56°C with the addition of 20% maltodextrin as a coating material. This study aimed to determine the shelf life of instant orange sweet potato probiotic powder using the Accelerated Shelf Life Testing (ASLT) method based on the Arrhenius equation model. The instant orange sweet potato probiotic powder was stored at temperatures of 4°C, 28°C, and 40°C for 56 days. The parameters observed every seven days were moisture content, pH, total acidity, and total lactic acid bacteria (LAB). The experimental results showed a linear relationship between the increase in moisture content and pH, and the decrease in total acidity and total LAB count over storage time at each temperature. The estimated shelf life of the instant orange sweet potato probiotic powder stored at 4°C, 28°C, and 40°C was 49, 45, and 43 days based on moisture content; 34, 42, and 46 days based on pH; 212, 207, and 206 days based on total acidity; and 236, 306, and 344 days based on total LAB, respectively. The shelf life of instant probiotic orange sweet potato powder can be determined using the ASLT method, with variations depending on the quality parameters evaluated.